Evaluation of the causes of Bukit Antarabangsa 2008 landslide by using fault tree analysis - Kazmi, D. (EDP Sciences, 2017)
Bukit Antarabangsa 2008 is considered as a deep-seated landslide which occurred in the landslide-prone area of Ulu Klang, Malaysia. The precipitation data obtained from previous studies show that there were comparatively less rainfalls immediately before the landslide which suggests that other potential triggers must be analyzed. This study analyses the causes of Bukit Antarabangsa 2008 landslide by performing fault tree analysis (FTA) which is a logical and diagrammatic method to evaluate the probability of an accident resulting from sequences and combinations of faults. The FTA is performed on four potential landslide contributors of improper shear strength parameters, flawed development plan, erroneous drainage planning & design and, ineffective slope strengthening works in order to determine the causes of the landslide. The analysis shows that the causes of Bukit Antarabangsa 2008 landslide potentially include ineffective slope strengthening works related to monitoring and maintenance which is followed by improper development plan having a probability of failure of 0.194 and 0.15 respectively. These causes actually correlate with the human errors which are often neglected during the slope construction and required to be addressed to increase the safety of the slopes. © The Authors, published by EDP Sciences, 2017.